Coronary Plaque Regression and Fractional Flow Reserve Improvement in a Chronic Coronary Syndrome Case: Early Optimal Medical Therapy and Fractional Flow Reserve-Computed Tomography Follow-Up Strategy - Yuki Yoshimitsu; Toru Awaya; Naoyuki Kawagoe; Taeko Kunimasa; Raisuke Iijima; Hidehiko Hara (Diseases)
Background: Optimal medical therapy (OMT) is increasingly recognized as a cornerstone in managing chronic coronary syndrome (CCS), offering a non-invasive alternative to percutaneous coronary intervention (PCI). Case Presentation: A 38-year-old male with diabetes, dyslipidemia, and hypertension was treated with early and comprehensive OMT, including statins, ezetimibe, sodium-glucose cotransporter 2 inhibitors (SGLT2i), pioglitazone, and renin-angiotensin system inhibitors. Insulin was introduced during the acute phase to stabilize glycemic control. His HbA1c decreased to 6.3% within 4 months. Results: Over 8 months, the patient experienced a reduction in coronary plaque burden and an improvement in fractional flow reserve (FFR) from 0.75 to 0.90, indicating enhanced coronary blood flow. Plaque volume burden decreased from 85% to 52% in key coronary segments. Conclusions: This case highlights the effectiveness of OMT, including statins, ezetimibe, SGLT2i, and pioglitazone, in achieving outcomes comparable to PCI. FFR-computed tomography follow-up is critical in guiding treatment decisions. Continued OMT is recommended if plaque stabilization is observed. If no improvement is observed, OMT should be intensified, and PCI considered as appropriate.